Cultural stressors and behavioral correlations of post-pandemic anxiety among Emirati university students - Webb, Heather; Abdulla, Ayesha; Fenech, Roberta; Dalky, Heyam F.; Mahmmod, Yasser; Chamoun, Joelle (Frontiers in Psychology, 2025)
This study investigates the prevalence and predictors of anxiety among Emirati university students in the post-pandemic period, focusing on the influence of socio-demographic variables, mental health comorbidities, and lifestyle behaviors. A cross-sectional online survey was conducted across 16 UAE public university campuses from November 2022 to February 2023, yielding 7,244 complete responses from students aged 18 and above. The survey assessed anxiety using the Generalized Anxiety Disorder 7-item (GAD-7) scale and included items on demographics, physical and mental health, support systems, and behavior patterns such as substance use and internet engagement. Multivariable logistic regression models examined associations between anxiety and key explanatory variables. Results revealed that 8% of respondents experienced severe anxiety, with significant associations observed between anxiety and gender, age, income, disability status, and physical health conditions. Females, younger individuals, those with household incomes below AED 10,000, and students with chronic illnesses or disabilities were at higher risk. Mental health comorbidities such as depression, panic attacks, eating disorders, OCD, and ADHD showed strong associations with anxiety severity. Furthermore, behavioral correlations including excessive internet use, gaming, alcohol consumption, and prescribed medication use were linked to elevated anxiety levels, although not all were statistically significant. Despite efforts to increase mental health awareness in the UAE, stigma and cultural norms remain barriers to help-seeking. The study underscores the need for culturally tailored mental health interventions that address stigma, promote early screening, and consider the role of maladaptive coping behaviors. Universities should implement accessible support systems that incorporate Arabic-language resources, peer mentoring, and family or religious engagement. These findings contribute to the global understanding of anxiety in higher education and highlight the importance of localized mental health strategies in post-pandemic recovery.